Contribution à la connaissance de la flore du Maroc septentrional : Maroc Atlantique nord, Rif, Littoral méditerranéen - Chambouleyron, Mathieu (Acta Botanica Malacitana, 2019)
Contribution to the knowledge of the flora of northern Morocco: Northern Atlantic Morocco, Rif, Mediterranean littoral Mots-clés: chorologie, flore vasculaire, Maroc septentrional. Keywords: chorology, vascular flora, northern Morocco.